The Invisible Hand of Open Collaboration: A Stakeholder Approach to Open Innovation And P2P-Production in The Renewable Energy Sector - Brentley, Austin Benjamin (2009)
Believing that renewable energy innovation is just one of many ways to wean humankind's dependence on fossil fuels, this paper explores alternative methods by which a firm may align the needs of those stakeholders (Inventers, Entrepreneurs, and Consumers) deemed critical to the creation and commercialization of renewable energy solutions. The literature suggests that innovative efforts are best served when Inventors work in peer-driven communities founded on open source principles, Entrepreneurs adopt open innovation in which they actively source R&D beyond their walls, and Consumers allow Inventors and Entrepreneurs to work harmoniously together. While all three stakeholder groups may be singularly focused on renewable energy innovation, combining them within one framework proves challenging due to competing interests regarding funding, intellectual property ownership, and governance. Instrumental stakeholder theory suggests that resolving these competing interests is a job best suited for a centralized firm capable of identifying, prioritizing, and balancing the different needs within the stakeholder constellation. However, the inclusion of this firm introduces one additional stakeholder (the shareholder) whose profit-maximization interests, by law, take priority over all others needs and interests. Using Delphi-inspired research methodology, this paper explores what might emerge if stakeholders created a self-sustaining system in which managerial decisions were governed solely by the renewable energy goals of Consumers, Inventors, and Entrepreneurs rather than by the profit-maximization goals of shareholders.